Influence of Darunavir: β-cyclodextrin complex on the solubility of Darunavir - Kogawa, Ana Carolina [UNESP]; Corrêa, Josilene Chaves Ruela [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2014)
Darunavir, a protease inhibitor used in the treatment of HIV infection, was complexed with β-cyclodextrin because of its low solubility in water and poor bioavailability, with the objective of improving the solubility of darunavir aiming subsequently the administration of lower doses and increasing patient adherence to the treatment. Children under seven are usually unable to swallow the solid medications, especially tablets 300, 400 or 600 mg, such as darunavir. To make adult medicines suitable for children, tablets or capsules are often processed to adjust dosages and facilitate swallowing, but in most cases they do not support the medication. Therefore, complexation developed is extremely interesting. The last World Health Assembly launched the global campaign „Make medicines child size‟. The determination of the solubility of drugs is a fundamental part in Biopharmaceutics Classification System. In this research purified water with pH 8.0, acetate buffer 0.05 M pH 4.5, phosphate buffer 0.2 M pH 6.8 and phosphate butter 0.05 M with 0.5 % Tween pH 3.0 were evaluated in the solubility of darunavir:β-cyclodextrin complex. In all dissolution media tested complex showed solubility at least 5 times greater than the free drug.
Keywords: Biopharmaceutics classification system; Child size; Darunavir: β-cyclodextrin; Solubility